2007
DOI: 10.1161/atvbaha.106.128793
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin Alters Platelet Aggregability in Patients With Hypercholesterolemia

Abstract: Background-Hypercholesterolemia enhances platelet aggregability. Statins have beneficial effects on cardiovascular events. The purpose of this study is to investigate whether statins inhibit platelet aggregation and, if so, the mechanisms. Methods and Results-Twelve patients with hypercholesterolemia were prospectively randomized in a crossover design to receive either fluvastatin (20 mg/d) or colestimide (3000 mg/d) for 12 weeks. The subjects were switched to the opposite arm for additional 12 weeks. Before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 43 publications
0
39
0
1
Order By: Relevance
“…4 Reduction of several markers of oxidative stress including isoprostanes, , and nitrotyrosine have been observed after statin treatment but the underlying mechanism is still unclear. [5][6][7][8][9] In a pilot study performed in patients with chronic granulomatous disease (X-CGD), a very rare life-threatening disease secondary to hereditary deficiency of gp91 phox (the catalytic subunit of phagocyte NADPH oxidase), we found a significant reduction of urinary isoprostanes. 10 Also, in children with hypercholesterolemia, we observed a significant correlation between platelet gp91 phox expression and urinary isoprostanes.…”
mentioning
confidence: 89%
“…4 Reduction of several markers of oxidative stress including isoprostanes, , and nitrotyrosine have been observed after statin treatment but the underlying mechanism is still unclear. [5][6][7][8][9] In a pilot study performed in patients with chronic granulomatous disease (X-CGD), a very rare life-threatening disease secondary to hereditary deficiency of gp91 phox (the catalytic subunit of phagocyte NADPH oxidase), we found a significant reduction of urinary isoprostanes. 10 Also, in children with hypercholesterolemia, we observed a significant correlation between platelet gp91 phox expression and urinary isoprostanes.…”
mentioning
confidence: 89%
“…Statins can also decrease platelet activation by modulating the NO bioavailability in platelets (Laufs et al, 2000;Haramaki et al, 2007;Lee et al, 2010) and rapidly reducing the CD36 and lectin-like ox-LDL receptor-1 (Mehta et al, 2001;Puccetti et al, 2005), specific receptors for ox-LDL that are considered potent platelets agonists. Furthermore, statins inhibit the platelet-induced tissue factor expression by monocytes and macrophages (Puccetti et al, 2000), counteracting the prothrombotic complications of atherosclerosis (Aikawa et al, 2001).…”
Section: Statins and Platelet Functionmentioning
confidence: 99%
“…[40] In a human study, fluvastatin was shown to decrease platelet aggregation in a mechanism thought to be mediated by increased platelet derived nitric oxide release. [41] In a rat model of streptozotocin-induced diabetes, rosuvastatin has been shown to reduce fibrinogen binding to activated GPIIb/IIIa and P-selectin surface expression on platelets. [42] In a small clinical study, 17 patients received atorvastatin 10mg/day, whereas 18 patients received no statin therapy.…”
Section: Thrombosismentioning
confidence: 99%